Potential of antimicrobial-producing endophytic bacteria from Balikpapan endemic ginger (Etlingera balikpapanensis A.D. Poulsen) - FATIMAH FATIMAH; LILLAH ASRITAFRIHA; SYARIFAH SALSABILA; ERNA KRISTIANA DEWI; NI’MATUZAHROH NI’MATUZAHROH; ALMANDO GERALDI; RICO RAMADHAN; HERY SUWITO; ARRIZAL RAHMAN; LUKMAN RIYADI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Fatimah, Asritafriha L, Salsabila S, Dewi EK, Ni’matuzahroh, Geraldi A, Ramadhan R, Suwito H, Rahman A, Riyadi L. 2024. Potential of antimicrobial-producing endophytic bacteria from Balikpapan endemic ginger (Etlingera balikpapanensis A.D. Poulsen). Biodiversitas 25: 3005-3013. Etlingera balikpapanensis A.D. Poulsen is a new species of the Zingiberaceae family, which was discovered as an endemic species in the Balikpapan, Kalimantan. This study aimed to isolate endophytic bacteria from endemic Balikpapan ginger (E. balikpapanensis) and evaluate its antimicrobial activity against Escherichia coli, Staphylococcus aureus, and Candida albicans and to identify the most promising antimicrobial isolates. Plant samples include roots, stems, and leaves. The process of isolating bacteria from various plant parts, such as roots, stems, and leaves, involved repeated subculturing until pure isolates were obtained. Seven pure isolates were successfully obtained, coded as 6D, 5R, 2R, 3D1, 10D, 4R2, and 2D. Macroscopic, microscopic, and biochemical characterization of the seven isolates was carried out. The seven endophytic bacteria had varied macroscopic characteristics and were Gram-positive. The disc diffusion method was used to determine the ability of isolates to produce antimicrobial agents. The isolates showed antibacterial activity against E. coli and S. aureus. Isolates 3D1 and 5R showed the highest antibacterial activity against E. coli (8.20±0.47 mm and 8.57±0.08 mm), and 5R also showed the highest antibacterial activity against S. aureus (8.14±0.49 mm). These results demonstrate the potential of these isolates as effective antimicrobial agents. The 16S rRNA gene analysis revealed that isolate 3D1 was identified as Bacillus cereus strain PJA4.2 and isolate 5R as Micrococcus luteus strain SGAir0127 with similarity of 99.55% and 100%, respectively.